Weather-resistant modified calcium carbonate as well as preparation method and application thereof
By coating the silicon sol on ultrafine calcium carbonate particles and performing polymethylsiloxane surface treatment to form a silica envelope, the problem of PVC profiles being prone to yellowing and brittle under ultraviolet irradiation is solved, and its weather resistance and UV aging resistance are significantly improved.
Patent Information
- Application Number
- CN202510149988.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-11
- Publication Date
- 2025-04-22
AI Technical Summary
In the prior art, PVC profiles are prone to yellowing and brittle under ultraviolet irradiation, which affects their service life and safety performance, and the added ultrafine calcium carbonate has insufficient weather resistance and ultraviolet aging resistance.
The ultrafine calcium carbonate particles are coated with silicon sol as a cover, and surface treatment is carried out by polymethylsiloxane to form a silica envelope to improve the weather resistance of the calcium carbonate particles.
It significantly improves the weather resistance and UV aging resistance of modified calcium carbonate, extends the service life of PVC profiles and improves its safety performance.
Smart Images

Figure CN119859319A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of powder materials, and in particular to a weather-resistant modified calcium carbonate and a preparation method and application thereof. Background Art
[0002] With the continuous promotion of replacing steel with plastic, outdoor doors and windows, fences, fences and other special-shaped materials are mostly made of PVC. PVC is prone to degradation under long-term exposure to ultraviolet rays, causing the products to turn yellow and brittle, thus affecting their service life. Although the aging time can be delayed by adding additives such as antioxidants, anti-aging agents and stabilizers, in order to improve the processing performance of PVC special-shaped materials and reduce production costs, PVC special-shaped materials generally require about 20% to 50% of ultrafine calcium carbonate for filling. Due to the general weather resistance and UV aging resistance of calcium carbonate, PVC profile products with added calcium carbonate are prone to yellowing and brittleness after long-term outdoor use, affecting their use effect and safety performance. The development of ultrafine calcium carbonate with aging resistance is of great significance to improving the aging resistance of PVC special-shaped materials. Summary of the invention
[0003] The purpose of the present invention is to overcome the problems in the prior art and provide a weather-resistant modified calcium carbonate and a preparation method and application thereof.
[0004] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0005] The present invention provides a method for preparing weather-resistant modified calcium carbonate, comprising the following steps:
[0006] (1) grinding calcium carbonate to obtain a semi-finished calcium carbonate product;
[0007] (2) mixing the semi-finished calcium carbonate product and the modified solution and then classifying them to obtain coated calcium carbonate;
[0008] (3) Surface treatment of coated calcium carbonate and polymethylsiloxane is performed to obtain the weather-resistant modified calcium carbonate.
[0009] Preferably, the particle size of the calcium carbonate in step (1) is 1 to 10 mm; and the average particle size D50 of the semi-finished calcium carbonate product is 10 to 13 μm.
[0010] Preferably, the modified solution in step (2) comprises silica sol and stearic acid emulsion; the mass ratio of the silica sol to the stearic acid emulsion is 5 to 6:1.
[0011] Preferably, the solid content of the silica sol is 10-12%; the solid content of the stearic acid emulsion is 20-40%.
[0012] Preferably, the mass of the modified solution in step (2) is 4-5% of the mass of the semi-finished calcium carbonate product.
[0013] Preferably, the mixing speed in step (2) is 20 to 25 rpm, the volume filling rate is 30 to 32%, and the mixing time is 35 to 40 min;
[0014] The rotation speed of the classification in step (2) is 4000-4150 rpm;
[0015] The specific surface area of the coated calcium carbonate in step (2) is ≥10m 2 / g.
[0016] Preferably, the mass of the polymethylsiloxane in step (3) is 1.5-2% of the mass of the coated calcium carbonate.
[0017] Preferably, the surface treatment in step (3) is carried out at a rotation speed of 60 to 70 rpm, a temperature of 110 to 120° C., and a time of 25 to 28 min.
[0018] The present invention also provides weather-resistant modified calcium carbonate prepared by the preparation method of the weather-resistant modified calcium carbonate.
[0019] The invention also provides application of the weather-resistant modified calcium carbonate in PVC profiles.
[0020] The present invention provides a method for preparing weather-resistant modified calcium carbonate, comprising the following steps: grinding calcium carbonate to obtain a semi-finished calcium carbonate product; mixing the semi-finished calcium carbonate product and a modified solution and then grading them to obtain coated calcium carbonate; and surface treating the coated calcium carbonate and polymethylsiloxane to obtain the weather-resistant modified calcium carbonate. The present invention uses silica sol as a coating body to coat the surface of ultrafine calcium carbonate particles, and then performs surface coating treatment with polymethylsiloxane to obtain the final silica-coated modified ultrafine calcium carbonate.
[0021] The product of the present invention adopts silica sol as a coating agent, which greatly improves the weather resistance of calcium carbonate particles, and can also play the role of a grinding aid during the grinding process, thereby improving the grinding efficiency and being conducive to obtaining ultrafine calcium carbonate particles with better fineness; the product of the present invention adopts a composite effect of stearic acid emulsion and silica sol, and the stearic acid emulsion acts on the calcium carbonate particles through mechanical force during the grinding process, and is coated on the surface of the calcium carbonate particles to form an organic film, thereby preventing the calcium carbonate particles from agglomerating, so as to obtain a better silicon dioxide coating effect.
[0022] The present invention adopts dry process production, and the water and stearic acid emulsion in the silica sol solution work together to play the role of wetting and dispersing, thereby obtaining ultrafine calcium carbonate with better fineness, and its specific surface area reaches 10m 2 / g or above, with good reinforcement effect. At the same time, polymethylsiloxane is used for modification to improve weather resistance. Since the surface of the calcium carbonate particles is coated with a layer of silicon dioxide, the modification effect is greatly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 It is a comparison chart of the PVC profile sample prepared in Example 1 after 500hUV accelerated aging and 1000hUV accelerated aging;
[0024] Figure 2 It is a comparison chart of the PVC profile sample prepared in Example 2 after 500hUV accelerated aging and 1000hUV accelerated aging;
[0025] Figure 3 It is a comparison chart of the PVC profile sample prepared in Example 3 after 500hUV accelerated aging and 1000hUV accelerated aging;
[0026] Figure 4 This is a comparison chart of the PVC profile sample prepared in Comparative Example 1 after 500hUV accelerated aging and 1000hUV accelerated aging;
[0027] Figure 5 This is a comparison chart of the PVC profile sample prepared in Comparative Example 2 after 500hUV accelerated aging and 1000hUV accelerated aging;
[0028] Figure 6 It is a comparison chart of the PVC profile sample prepared in Comparative Example 3 after 500hUV accelerated aging and 1000hUV accelerated aging;
[0029] Figure 7 This is a comparison chart of the PVC profile sample prepared in Comparative Example 4 after 500hUV accelerated aging and 1000hUV accelerated aging. DETAILED DESCRIPTION
[0030] The present invention provides a method for preparing weather-resistant modified calcium carbonate, comprising the following steps:
[0031] (1) grinding calcium carbonate to obtain a semi-finished calcium carbonate product;
[0032] (2) mixing the semi-finished calcium carbonate product and the modified solution and then classifying them to obtain coated calcium carbonate;
[0033] (3) Surface treatment of coated calcium carbonate and polymethylsiloxane is performed to obtain the weather-resistant modified calcium carbonate.
[0034] In the present invention, the raw material of calcium carbonate is calcite, which is crushed twice by a jaw crusher and a cone crusher, and the calcium carbonate is obtained by adjusting the screen size of the crushing equipment.
[0035] In the present invention, the particle size of the calcium carbonate in step (1) is preferably 1 to 10 mm, more preferably 2 to 8 mm, and more preferably 4 to 6 mm.
[0036] In the present invention, calcium carbonate is preliminarily ground using a vertical roller mill, and the particle size is controlled by an airflow classifier provided in the mill to obtain a semi-finished calcium carbonate product; the average particle size D50 of the semi-finished calcium carbonate product is preferably 10 to 13 μm, more preferably 10.5 to 11.5 μm, and more preferably 10.8 to 11.2 μm; and the 2 μm content is preferably ≤25%, more preferably ≤24%, and more preferably ≤23%.
[0037] In the present invention, the modified solution in step (2) comprises silica sol and stearic acid emulsion; the mass ratio of the silica sol to stearic acid emulsion is preferably 5-6:1, more preferably 5.2-5.8:1, and more preferably 5.4-5.6:1.
[0038] In the present invention, the solid content of the silica sol is preferably 10-12%, more preferably 10.5-11.5%, more preferably 10.8-11.2%; the solid content of the stearic acid emulsion is preferably 20-40%, more preferably 25-35%, more preferably 28-32%.
[0039] In the present invention, silica sol and stearic acid emulsion are stirred uniformly to obtain a modified solution.
[0040] In the present invention, the mass of the modified solution in step (2) is preferably 4-5% of the mass of the semi-finished calcium carbonate product, more preferably 4.2-4.8%, and more preferably 4.4-4.6%.
[0041] In the present invention, the modified solution and the semi-finished calcium carbonate product are mixed in a spiral mixer and then fed into a drum ball mill for mixing. The purpose of mixing here is grinding.
[0042] In the present invention, the mixing speed in step (2) is preferably 20 to 25 rpm, more preferably 21 to 24 rpm, and more preferably 22 to 23 rpm; the volume filling rate is preferably 30 to 32%, more preferably 30.5 to 31.5%, and more preferably 30.8 to 31.2%; the time is preferably 35 to 40 min, more preferably 36 to 39 min, and more preferably 37 to 38 min.
[0043] In the present invention, after the mixing is completed, the mixed material is fed into a single-rotor vertical airflow classifier for classification.
[0044] In the present invention, the rotation speed of the classification in step (2) is preferably 4000-4150 rpm, more preferably 4050-4100 rpm, and even more preferably 4080-4090 rpm.
[0045] The specific surface area of the coated calcium carbonate in step (2) is preferably ≥10m 2 / g, more preferably ≥12m 2 / g, more preferably ≥15m 2 / g; the maximum particle size of coated calcium carbonate is less than 10μm, and the 2μm content is ≥85%.
[0046] In the present invention, the mass of the polymethylsiloxane in step (3) is preferably 1.5-2% of the mass of the coated calcium carbonate, more preferably 1.6-1.9%, and even more preferably 1.7-1.8%.
[0047] In the present invention, the rotation speed of the surface treatment in step (3) is preferably 60-70 rpm, more preferably 62-68 rpm, more preferably 64-66 rpm; the temperature is preferably 110-120°C, more preferably 112-118°C, more preferably 114-116°C; the time is preferably 25-28 min, more preferably 25.5-27.5 min, more preferably 26-27 min.
[0048] In the present invention, the surface treatment is completed and the sample is left to stand at a temperature for a period of preferably 20 to 25 minutes, more preferably 21 to 24 minutes, and even more preferably 22 to 23 minutes.
[0049] The present invention also provides weather-resistant modified calcium carbonate prepared by the preparation method of the weather-resistant modified calcium carbonate.
[0050] The invention also provides application of the weather-resistant modified calcium carbonate in PVC profiles.
[0051] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0052] Example 1
[0053] 1) using calcite as a raw material, crushing it twice by a jaw crusher + a cone crusher, adjusting the size of the crushing equipment screen to obtain calcium carbonate particles with a particle size between 1 and 10 mm, and using a vertical roller mill to grind the crushed particles preliminarily, and using an airflow classifier provided by the mill to control the 2 μm content of the ground calcium carbonate particles to be 25%, and the average particle size D50 of the calcium carbonate semi-finished product to be 10 μm;
[0054] 2) mixing a silica sol having a solid content of 12% and a stearic acid emulsion having a solid content of 30% at a ratio of 5:1 in a stirring tank at room temperature to obtain a modified solution;
[0055] 3) Add the modified solution to the semi-finished calcium carbonate product, and after the two are fully mixed by a spiral mixer, feed them into a drum ball mill for ultrafine grinding, wherein the mass of the modified solution is 5% of the mass of the semi-finished calcium carbonate product, and the size of the horizontal ball mill is preferably 3.2m in diameter and 6m in length; the speed of the ball mill is preferably 23rpm, the volume filling rate of the grinding medium is 32%, and the grinding time is 35min. After ultrafine grinding in the ball mill, feed it into a single-rotor vertical airflow classifier, the diameter of the classifier wheel is 500mm, and the speed of the classifier wheel is controlled to be 4150rpm, thereby obtaining coated calcium carbonate (specific surface area ≥10m 2 / g, maximum particle size less than 10μm, 2μm content ≥85%).
[0056] 4) The coated calcium carbonate is fed into a temperature-controllable low-speed mixer with a diameter of 1500 mm, the speed of the mixer is 60 r / min, the temperature of the mixer is controlled at 120° C. 1.5% polymethylsiloxane is added for surface treatment, the stirring time is 25 min, and after stirring, the mixture is kept warm and allowed to stand for 20 min to obtain a weather-resistant modified calcium carbonate.
[0057] Example 2
[0058] 1) using calcite as a raw material, crushing it twice by a jaw crusher + a cone crusher, adjusting the size of the crushing equipment screen to obtain calcium carbonate particles with a particle size between 1 and 10 mm, and using a vertical roller mill to grind the crushed particles preliminarily, and using an airflow classifier provided by the mill to control the 2 μm content of the ground calcium carbonate particles to be 20%, and the average particle size D50 of the calcium carbonate semi-finished product to be 11 μm;
[0059] 2) mixing a silica sol having a solid content of 10% and a stearic acid emulsion having a solid content of 25% in a ratio of 6:1 in a stirring tank at room temperature to obtain a modified solution;
[0060] 3) Add the modified solution to the semi-finished calcium carbonate product, and after the two are fully mixed by a spiral mixer, feed them into a drum ball mill for ultrafine grinding, wherein the mass of the modified solution is 4% of the mass of the semi-finished calcium carbonate product, and the size of the horizontal ball mill is preferably 3.0m in diameter and 5.5m in length; the speed of the ball mill is preferably 20rpm, the volume filling rate of the grinding medium is 31%, and the grinding time is 40min. After ultrafine grinding in the ball mill, feed it into a single-rotor vertical airflow classifier, the diameter of the classifier wheel is 500mm, and the speed of the classifier wheel is controlled to be 4000rpm, thereby obtaining coated calcium carbonate (specific surface area ≥11m 2 / g, maximum particle size less than 8μm, 2μm content ≥88%).
[0061] 4) The coated calcium carbonate is fed into a temperature-controllable low-speed mixer with a diameter of 1500 mm, the speed of the mixer is 70 r / min, the temperature of the mixer is controlled at 110° C., 1.8% polymethylsiloxane is added for surface treatment, the stirring time is 25 min, and after stirring, the mixture is kept warm and allowed to stand for 25 min to obtain a weather-resistant modified calcium carbonate.
[0062] Example 3
[0063] 1) using calcite as a raw material, crushing it twice by a jaw crusher + a cone crusher, adjusting the size of the crushing equipment screen to obtain calcium carbonate particles with a particle size between 1 and 10 mm, and using a vertical roller mill to grind the crushed particles preliminarily, and using an airflow classifier provided by the mill to control the 2 μm content of the ground calcium carbonate particles to be 22%, and the average particle size D50 of the calcium carbonate semi-finished product to be 13 μm;
[0064] 2) mixing a silica sol having a solid content of 11% and a stearic acid emulsion having a solid content of 35% at a ratio of 5.5:1 in a stirring tank at room temperature to obtain a modified solution;
[0065] 3) Add the modified solution to the semi-finished calcium carbonate product, and after the two are fully mixed by a spiral mixer, feed them into a drum ball mill for ultrafine grinding, wherein the mass of the modified solution is 4.5% of the mass of the semi-finished calcium carbonate product, and the size of the horizontal ball mill is preferably 3.0m in diameter and 5.5m in length; the speed of the ball mill is preferably 23rpm, the volume filling rate of the grinding medium is 32%, and the grinding time is 40min. After ultrafine grinding in the ball mill, feed it into a single-rotor vertical airflow classifier, the diameter of the classifier wheel is 500mm, and the speed of the classifier wheel is controlled to be 4100rpm, thereby obtaining coated calcium carbonate (specific surface area ≥12m 2 / g, maximum particle size less than 10μm, 2μm content ≥87%).
[0066] 4) The coated calcium carbonate is fed into a temperature-controllable low-speed mixer with a diameter of 1500 mm, the speed of the mixer is 65 r / min, the temperature of the mixer is controlled at 115° C., 1.5% polymethylsiloxane is added for surface treatment, the stirring time is 25 min, and after stirring, the mixture is kept warm and allowed to stand for 25 min to obtain a weather-resistant modified calcium carbonate.
[0067] Comparative Example 1
[0068] 1) using calcite as a raw material, crushing it twice by a jaw crusher + a cone crusher, adjusting the size of the crushing equipment screen to obtain calcium carbonate particles with a particle size between 1 and 10 mm, and using a vertical roller mill to grind the crushed particles preliminarily, and using an airflow classifier provided by the mill to control the 2 μm content of the ground calcium carbonate particles to be 22%, and the average particle size D50 of the calcium carbonate semi-finished product to be 13 μm;
[0069] 2) Adding silica sol with a solid content of 11% to the semi-finished calcium carbonate product, the two are fully mixed in a spiral mixer and then fed into a drum ball mill for ultrafine grinding, wherein the mass of the silica sol is 4.5% of the mass of the semi-finished calcium carbonate product, and the size of the horizontal ball mill is preferably 3.0m in diameter and 5.5m in length; the speed of the ball mill is preferably 23rpm, the volume filling rate of the grinding medium is 32%, and the grinding time is 40min. After ultrafine grinding in the ball mill, it is fed into a single-rotor vertical airflow classifier, the diameter of the classifier wheel is 500mm, and the speed of the classifier wheel is controlled to be 4100rpm, thereby obtaining coated calcium carbonate.
[0070] 3) The coated calcium carbonate is fed into a temperature-controllable low-speed mixer with a diameter of 1500 mm, the speed of the mixer is 65 r / min, the temperature of the mixer is controlled at 115° C., 1.5% polymethylsiloxane is added for surface treatment, the stirring time is 25 min, and after stirring, the mixture is kept warm and allowed to stand for 25 min to obtain a weather-resistant modified calcium carbonate.
[0071] Comparative Example 2
[0072] 1) using calcite as a raw material, crushing it twice by a jaw crusher + a cone crusher, adjusting the size of the crushing equipment screen to obtain calcium carbonate particles with a particle size between 1 and 10 mm, and using a vertical roller mill to grind the crushed particles preliminarily, and using an airflow classifier provided by the mill to control the 2 μm content of the ground calcium carbonate particles to be 22%, and the average particle size D50 of the calcium carbonate semi-finished product to be 13 μm;
[0073] 2) Add stearic acid emulsion with a solid content of 30% to the semi-finished calcium carbonate product, and after being fully mixed by a spiral mixer, feed the product to a drum ball mill for ultrafine grinding, wherein the mass of the stearic acid emulsion is 4.5% of the mass of the semi-finished calcium carbonate product, and the size of the horizontal ball mill is preferably 3.0m in diameter and 5.5m in length; the rotation speed of the ball mill is preferably 23rpm, the volume filling rate of the grinding medium is 32%, and the grinding time is 35min. After ultrafine grinding in the ball mill, feed the product to a single-rotor vertical airflow classifier, the diameter of the classifier wheel is 500mm, and the rotation speed of the classifier wheel is controlled to be 4100rpm, thereby obtaining coated calcium carbonate.
[0074] 3) The coated calcium carbonate is fed into a temperature-controllable low-speed mixer with a diameter of 1500 mm, the speed of the mixer is 65 r / min, the temperature of the mixer is controlled at 115° C., 1.5% polymethylsiloxane is added for surface treatment, the stirring time is 25 min, and after stirring, the mixture is kept warm and allowed to stand for 25 min to obtain a weather-resistant modified calcium carbonate.
[0075] Comparative Example 3
[0076] 1) using calcite as a raw material, crushing it twice by a jaw crusher + a cone crusher, adjusting the size of the crushing equipment screen to obtain calcium carbonate particles with a particle size between 1 and 10 mm, and using a vertical roller mill to grind the crushed particles preliminarily, and using an airflow classifier provided by the mill to control the 2 μm content of the ground calcium carbonate particles to be 22%, and the average particle size D50 of the calcium carbonate semi-finished product to be 13 μm;
[0077] 2) Add the commercially available imported grinding aid modifier SL-48 to the semi-finished calcium carbonate product, and after the two are fully mixed by a spiral mixer, feed them into a drum ball mill for ultrafine grinding, wherein the mass of the commercially available imported grinding aid modifier SL-48 is 4.5% of the mass of the semi-finished calcium carbonate product, and the size of the horizontal ball mill is preferably 3.0m in diameter and 5.5m in length; the speed of the ball mill is preferably 23rpm, the volume filling rate of the grinding medium is 32%, and the grinding time is 35min. After ultrafine grinding in the ball mill, feed them into a single-rotor vertical airflow classifier, the diameter of the classifier wheel is 500mm, and the speed of the classifier wheel is controlled to be 4100rpm, thereby obtaining coated calcium carbonate.
[0078] 3) The coated calcium carbonate is fed into a temperature-controllable low-speed mixer with a diameter of 1500 mm, the speed of the mixer is 65 r / min, the temperature of the mixer is controlled at 115° C., 1.5% polymethylsiloxane is added for surface treatment, the stirring time is 25 min, and after stirring, the mixture is kept warm and allowed to stand for 25 min to obtain a weather-resistant modified calcium carbonate.
[0079] Comparative Example 4
[0080] 1) using calcite as a raw material, crushing it twice by a jaw crusher + a cone crusher, adjusting the size of the crushing equipment screen to obtain calcium carbonate particles with a particle size between 1 and 10 mm, and using a vertical roller mill to grind the crushed particles preliminarily, and using an airflow classifier provided by the mill to control the 2 μm content of the ground calcium carbonate particles to be 22%, and the average particle size D50 of the calcium carbonate semi-finished product to be 13 μm;
[0081] 2) mixing a silica sol having a solid content of 11% and a stearic acid emulsion having a solid content of 30% at a ratio of 5.5:1 in a stirring tank at room temperature to obtain a modified solution;
[0082] 3) Add the modified solution to the semi-finished calcium carbonate product, and after the two are fully mixed by a spiral mixer, feed them into a drum ball mill for ultrafine grinding, wherein the mass of the modified solution is 4.5% of the mass of the semi-finished calcium carbonate product, and the size of the horizontal ball mill is preferably 3.0m in diameter and 5.5m in length; the speed of the ball mill is preferably 23rpm, the volume filling rate of the grinding medium is 32%, and the grinding time is 35min. After ultrafine grinding in the ball mill, feed it into a single-rotor vertical airflow classifier, the diameter of the classifier wheel is 500mm, and the speed of the classifier wheel is controlled to be 4100rpm, thereby obtaining coated calcium carbonate (specific surface area ≥12m 2 / g, maximum particle size less than 10μm, 2μm content ≥87%).
[0083] 4) The coated calcium carbonate is fed into a temperature-controlled low-speed mixer with a diameter of 1500 mm, the speed of the mixer is 65 r / min, the temperature of the mixer is controlled at 115° C., 2% stearic acid 1865 is added for surface treatment, the stirring time is 25 min, and after stirring, the mixture is kept warm and allowed to stand for 25 min to obtain a weather-resistant modified calcium carbonate.
[0084] The modified calcium carbonate prepared in the examples and comparative examples was used to prepare PVC profiles according to the preparation formula in Table 1.
[0085] Table 1 Preparation formula
[0086] name PVC Stabilizer CPE Anti-aging agents DOP Titanium dioxide Modified calcium carbonate Added amount / mass 100 3 10 2 10 5 50
[0087] The stabilizer is a complex of calcium stearate and zinc stearate, and the mass ratio of calcium stearate to zinc stearate is 2:1;
[0088] The model of the antioxidant is UV-P, and its ingredient is benzotriazole.
[0089] The prepared samples were tested for performance and the results are recorded in Table 2.
[0090] Table 2 Performance test results
[0091]
[0092]
[0093] The comparison of the PVC profile samples prepared in Example 1 after 500hUV accelerated aging and 1000hUV accelerated aging is shown in the figure below: Figure 1 As shown; the comparison of the PVC profile samples prepared in Example 2 under 500hUV accelerated aging and 1000hUV accelerated aging is shown in Figure 2 As shown; the comparison of the PVC profile samples prepared in Example 3 after 500hUV accelerated aging and 1000hUV accelerated aging is shown in Figure 3As shown; Comparative Example 1 prepared PVC profile samples in 500hUV ultraviolet accelerated aging and 1000hUV ultraviolet accelerated aging comparison diagram as shown Figure 4 As shown; Comparative Example 2 prepared PVC profile samples in 500hUV accelerated aging and 1000hUV accelerated aging comparison diagram as shown Figure 5 As shown; Comparative Example 3 prepared PVC profile samples in 500hUV ultraviolet accelerated aging and 1000hUV ultraviolet accelerated aging comparison diagram as shown Figure 6 As shown; Comparative Example 4 prepared PVC profile samples in 500hUV ultraviolet accelerated aging and 1000hUV ultraviolet accelerated aging comparison diagram as shown Figure 7 shown. Figure 1 to Figure 7 In the figure, the left side shows the effect of 500hUV accelerated aging, and the right side shows the effect of 1000hUV accelerated aging.
[0094] It can be seen from the above embodiments that the present invention adopts a simpler process, innovatively uses silica sol and stearic acid emulsion to encapsulate calcium carbonate, obtains ultrafine calcium carbonate with ultrahigh fineness and high specific surface area by a dry process, and uses polymethylsiloxane to organically modify the encapsulated ultrafine calcium carbonate to further improve its weather resistance, and finally obtains ultrafine calcium carbonate with excellent weather resistance, which is applied to PVC profiles, greatly improving the weather resistance of the profiles.
[0095] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing weather-resistant modified calcium carbonate, characterized in that: It includes the following steps: (1) grinding calcium carbonate to obtain a semi-finished calcium carbonate product; (2) mixing the semi-finished calcium carbonate product and the modified solution and then classifying them to obtain coated calcium carbonate; (3) Surface treatment of coated calcium carbonate and polymethylsiloxane is performed to obtain the weather-resistant modified calcium carbonate.
2. The method for preparing weather-resistant modified calcium carbonate according to claim 1, wherein The particle size of the calcium carbonate in step (1) is 1 to 10 mm; the average particle size D50 of the semi-finished calcium carbonate product is 10 to 13 μm.
3. The preparation method of weather-resistant modified calcium carbonate according to claim 1 or 2, characterized in that, The modified solution in step (2) comprises silica sol and stearic acid emulsion; the mass ratio of the silica sol to the stearic acid emulsion is 5 to 6:
1.
4. The method for preparing weather-resistant modified calcium carbonate according to claim 3, wherein: The solid content of the silica sol is 10-12%; the solid content of the stearic acid emulsion is 20-40%.
5. The method for preparing the weather-resistant modified calcium carbonate according to claim 1 or 4, wherein: The mass of the modified solution in step (2) is 4-5% of the mass of the semi-finished calcium carbonate product.
6. The method for preparing weather-resistant modified calcium carbonate according to claim 5, characterized in that: In step (2), the mixing speed is 20-25 rpm, the volume filling rate is 30-32%, and the mixing time is 35-40 min; The rotation speed of the classification in step (2) is 4000-4150 rpm; The specific surface area of the coated calcium carbonate in step (2) is ≥10m 2 / g.
7. The method for preparing the weather-resistant modified calcium carbonate according to claim 1, 2, 4 or 6, characterized in that: The mass of the polymethylsiloxane in step (3) is 1.5-2% of the mass of the coated calcium carbonate.
8. The method for preparing weather-resistant modified calcium carbonate according to claim 7, wherein: The surface treatment in step (3) is carried out at a rotation speed of 60 to 70 rpm, a temperature of 110 to 120° C., and a time of 25 to 28 min.
9. The weather-resistant modified calcium carbonate prepared by the method for preparing the weather-resistant modified calcium carbonate according to any one of claims 1 to 8.
10. Use of the weather-resistant modified calcium carbonate according to claim 9 in PVC profiles.